Design of B1pF-A Large Aperture Dipole Magnet for EIC - Kurian, Febin; Amm, Kathleen; Anerella, Michael; Joshi, Piyush; Gupta, Ramesh; Witte, Holger; Marinozzi, Vittorio; Ambrosio, Giorgio (IEEE transactions on applied superconductivity, 2024)
The design of interaction region (IR) magnets for the Electron Ion Collider (EIC), demands tight boundary conditions on the magnet design given by the high field requirements and the proximity of electron and hadron beams within a common yoke and resultant crosstalk. This article discusses the electromagnetic design of the superconducting collared magnet B1pF. The magnet will be built as the prototype for several collared magnets (dipoles and quadrupoles) for the hadron beam in the forward direction of the IR. The magnet design is based on a single layer coil with an inner diameter of 300 mm over a slot length of 3 m. The magnet produces an integral field of 10.34 T.m at a current of 11.9 kA to produce a nominal field of about 3.96 T at its center. Given by the common Rutherford cable parameters, the magnet will be used as a baseline for optimization of all the collared magnets. The article further discusses yoke optimizations, quench analysis, coil end design and efforts on fine tuning of field quality.